Reception of work flexibility policies in MNCs : A case study of the relationship between organisational culture and work flexibility - Stolt, Tara (My University, 2022)
The purpose of the study is to find an answer to the following research question “How organisational culture and work flexibility are included in work flexibility policies?” The study was conducted as a single case study and the focus was on Finland and Sweden. Work flexibility, including both temporal and spatial flexibility, has been brought up and developed more than before during the last years. As a result of the pandemic employees and employers started to think again how work can and should be done regarding the location and time. In addition, younger generations’ expectations on work life may differ greatly considering the ways of doing work so employers need to adapt to that to some extent. Work flexibility is considered to be part of HR practices and policies. Work flexibility in Finland and Sweden can be quite freely adjusted by each employer how they want to use it with the exception that work time flexibility has some guidelines in the law in both countries. Organisational culture is often studied through cultural dimensions or competing values framework (CVF). As the cultural dimensions for this study were chosen people orientation, team orientation, aggressiveness, stability, innovation & risk taking, attention to detail, outcome orientation, level of control, professional orientation, openness, masculine versus feminine orientation and short-term versus long-term orientation. These dimensions were looked together with the CVF models’ culture type clan, adhocracy, hierarchy, and market. The study was conducted by using primary and secondary data which included interviews and internal communication materials. Based on the results of the study it can be stated that work flexibility policies have effects on work-family balance, work-life balance, and everyday work. The dominant culture type in the case company was clan which highlights that the organisation is an extension to family, leadership is nurturing, employee management is characterized by teamwork, organisation is seen to be held together by loyalty, trust and personal commitment and the key to success is in human resources. All these values can be seen similar to the responses that were highlighted in the answers considering work flexibility. Therefore, it can be stated that the relationship between the work flexibility and the culture is clear. In addition, during the interviews many answered that they as employees also saw work flexibility as a part of the culture and that the current work flexibility supports the same values as they have within the culture. As there were no previous studies on the subject this conclusion adds to the existing literature a new point of view. It could be argued that if these values within work flexibility and organisational culture are not in line it could result in some conflicting thoughts towards one or another especially now that work flexibility is so largely discussed. The interviewees all thought that they would not feel comfortable losing the work flexibility options they now have, and which work well.

Tutkimuksen tarkoituksena on löytää yhteys työn jouston ja organisaatiokulttuurin välillä vastaamalla seuraavaan tutkimuskysymykseen: ”Miten työn jousto ja organisaatiokulttuuri liittyvät toisiinsa?” Tutkimuskysymystä lähestytään työn joustavuuteen suhtautumisen kautta, tarkastellen ilmiötä case-yrityksen Suomen ja Ruotsin yksiköissä. Työn jouston menetelmiä (sekä aikaan että sijaintiin liittyviä) on nostettu esille ja kehitetty viime vuosina enemmän kuin aiemmin. Pandemian takia työnantajat ja työntekijät alkoivat miettiä uusiksi, miten työtä voidaan ja tulisi tehdä aikaa ja sijaintiin liittyen. Lisäksi nuorempien sukupolvien odotukset eroavat aiempien sukupolvien odotuksista työelämään. Työn jouston menetelmien nähdään olevan osa henkilöstöhallinnon käytäntöjä ja linjauksia. Työnantaja voi pääsääntöisesti vapaasti säädellä työnjoustoa Suomessa ja Ruotsissa kuitenkin sillä poikkeuksella, että työaikaan on muutamia sääntöjä lain puolesta. Organisaatiokulttuuria tutkitaan usein kulttuuridimensioiden tai CVF (competing values framëwork) mallin avulla. Tämän tutkimuksen kulttuuridimensioiksi valittiin henkilöorientaatio, tiimiorientaatio, aggressiivisuus, vakaus, innovaatioiden ja riskien ottaminen, yksityiskohtien huomioiminen, lopputulos orientaatio, kontrollin taso, ammatillinen orientaatio, avoimuus, maskuliininen tai feminiininen orientaatio ja lyhyen tai pitkän aikavälin orientaatio. Näitä dimensioita katsottiin yhdessä CVF mallin kulttuurityyppien kanssa, jotka ovat klaani, adhokratia, hierarkia ja markkina. Tutkimuksen empiirisenä datana käytettiin haastatteluja ja yrityksen sisäisiä viestintämateriaaleja. Tutkimuksessa selvisi, että nykyisten työnjouston menetelmien nähtiin vaikuttavan työn ja perheen yhdistämisessä, työn ja muun elämän yhdistämisessä sekä jokapäiväisessä työnteossa. Pääasiallinen kulttuurityyppi oli esimerkkiyrityksessä klaanikulttuuri, joka ilmaisee yrityksen olevan jatke perheelle ja tärkeitä arvoja ovat tiimityö, luottamus, lojaalisuus ja sitoutuminen. Sekä työn jouston että organisaatiokulttuurin nähtiin nostavan esille samoja arvoja. Voidaankin todeta, että työn joustolla ja organisaatiokulttuurilla nähdään olevan yhteys arvojen kautta. Lisäksi haastattelujen yhteydessä haastateltavat nostivat itsekin esille, että kokevat työn jouston menetelmien olevan osa organisaatiokulttuuria. He myös kokivat, että nykyiset menetelmät tukevat olemassa olevaa kulttuuria.
Keywords: work flexibility, flexible work arrangements, organisational culture